Passive vibration control of pipe-in-pipe (PIP) Systems subjected to vortex induced vibration (VIV) - Nikoo, H.; Bi, Kaiming; Hao, H. (2017)
This paper proposes using modified pipe-in-pipe (PIP) system to mitigate vortex induced vibration (VIV). Numerical simulations are carried out to examine the effectiveness of the proposed method. Firstly, a semi-empirical oscillator model is developed and validated by an experimental test of a single pipe. The validated model is then extended to the modified PIP system, which is simplified as a structure-tuned mass damper (TMD) system in present study. The governing equation of vibration is solved in the time domain using MATLAB/Simulink programming. The results demonstrate that the carefully designed PIP system can significantly suppress VIV of offshore cylindrical structures up to 84%.